Fostering International Student Success in Higher Education, Second Edition - Dowling , Trisha (Journal of International Students, 2023)
The second edition of Fostering International Student Success in Higher Education provides educators and administrators with clear and accessible resources to support international students. The authors highlight the ethical importance of an asset-based approach to education, which focuses on what students can do rather than what they are lacking. The book shares many practical classroom activities that follow this approach, such as linguistically responsive and antiracist teaching methods. The book also discusses opportunities that institutions can provide to foster community-connected learning and cross-cultural interaction. Both new educators and seasoned professionals working with international students will find this book a useful guide for their profession.